Preparation and characterization of compatibilized polypropylene / poly (acrylonitrile-butadiene-styrene) blends and nanocomposites - Ibrahim, Mohamad Al Hafiz (2013)
Polypropylene (PP)/poly(acrylonitrile-butadiene-styrene) (ABS) copolymer blends containing organophilic layered silicates montmorillonite (MMT) compatibilized with polypropylene-grafted-maleic anhydride (PP-g-MA) were prepared by means of melt extrusion using twin screw extruder followed by injection molding in order to examine the mechanical, morphological and thermal properties of the blends and nanocomposites. For PP/ABS blends, the loadings of ABS were varied from 20 to 50 wt% and the optimum formulation of 40 wt% of ABS was chosen based on the balance of stiffness and toughness which then compatibilized with 2, 4 and 6 phr of PP-g-MA. The nanocomposites were produced by the addition of 3 and 5 phr MMT into PP/ABS/PP-g-MA. The results showed that the incorporation of MMT in PP/ABS nanocomposites leads to higher stiffness but at the expense of toughness and strength. Meanwhile, the incorporation of PP-g-MA increased the stiffness and strength but the toughness was reduced. Morphological study revealed the two-phase morphology which was clearly visible for PP/ABS blend system. The dispersed phase of ABS was decreased as the amount of PP-g-MA increased. X-ray diffraction (XRD) and transmission electron microscopy (TEM) results showed the formation of nanocomposites as the MMT was intercalated by PP macromolecules. Incorporation of PP-g-MA has improved the degree of intercalation and hence resulting in better dispersion in PP/ABS. Thermogravimetric analysis (TGA) showed that the thermal stability significantly increased with the incorporation of MMT and further improvement in thermal stability was observed as the PP-g-MA was incorporated in PP/ABS nanocomposites. Differential scanning calorimetry (DSC) results showed that the degree of crystallinity (Xc) increased substantially with MMT content while maintaining its melting temperature (Tm). Further improvement was observed upon addition of PP-g-MA. Dynamic mechanical analysis (DMA) showed that the storage modulus increased with MMT content for compatibilized PP/ABS system compared to uncompatibilized system.